PENGAWASAN ANGKUTAN UMUM DALAM TERMINAL - Herianto, Sugeng; Widodo, Ernu; Marwiyah, Siti (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This normative juridical study analyzes the supervision of public transportation in terminals as an implementation of the state's constitutional duty to provide safe and high-quality public services. The research examines the legal basis, authority, and supervisory mechanisms regulated by Law No. 22 of 2009 on Road Traffic and Transport and other relevant regulations. The analysis reveals that while the regulatory framework is comprehensive, the effectiveness of field supervision faces significant challenges. Primary issues include inconsistent law enforcement, limited resources, and insufficient inter-agency coordination, all of which impede the core objectives of supervision: safety and order. These findings recommend a necessary transformation in the supervisory approach, specifically through the digitalization of processes, strengthened sanctions, and enhanced synergy among authorities. These measures are critical for addressing legal and implementation gaps, ensuring legal certainty, and protecting the rights of public transport users